Metagenome-assembled genome (MAG) of Oceancaulis alexandrii NP7 isolated from Mediterranean Sea polluted marine sediments and its bioremediation potential. Issue 9 (26th June 2021) - Dell'Anno, Filippo; van Zyl, Leonardo Joaquim; Trindade, Marla; Brunet, Christophe; Dell'Anno, Antonio; Ianora, Adrianna; Sansone, Clementina
Abstract: Oceanicaulis alexandrii strain NP7 is a marine bacterium which belongs to the Hyphomonadaceae family and was isolated from sediments highly contaminated with metals and polycyclic aromatic hydrocarbons released for decades by industrial activities in the Gulf of Naples (Mediterranean Sea). Here, we report the partial genome sequence and annotation of O. alexandrii strain NP7 that contains a chromosome of 2, 954, 327 bp and encodes for 2914 predicted coding sequences (CDSs) and 44 RNA-encoding genes. Although the presence of some CDSs for genes involved in hydrocarbon degradation processes ( e.g., alkB ) have already been described in the literature associated with the Oceanicaulis, this is the first time that more than 100 genes involved in metal detoxification processes and hydrocarbon degradation are reported belonging to this genus. The presence of a heterogeneous set of genes involved in stress response, hydrocarbon degradation, heavy metal resistance, and detoxification suggests a possible role for O. alexandrii NP7 in the bioremediation of these highly contaminated marine sediments.